The genotoxic, cytotoxic and growth regulatory effects of plant secondary metabolite β-caryophyllene on polyphagous pest Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae). (November 2022) - Mahajan, Evani; Singh, Sumit; Diksha,; Kaur, Sanehdeep; Sohal, Satwinder Kaur
Abstract: Use of secondary metabolites as an alternative to organic pesticides is an eco-friendly and safe strategy in pest management. β-caryophyllene [(1 R, 4 E, 9 S )-4, 11, 11-trimethyl-8-methylene bicyclo [7.2.0]undec-4-ene], a natural sesquiterpene is found as an essential oil in many plants like Syzygium aromaticum, Piper nigrum, Cannabis sativa . The present study aims at exploring the insecticidal, genotoxic and cytotoxic potential of β-caryophyllene against common cutworm Spodoptera litura (Fab.), a major polyphagous pest. S. litura larvae were fed on different concentrations (5, 25, 125, 625 and 3125 ppm) of β-caryophyllene. Results revealed delay in larval and pupal period with increase in concentration. Larval mortality increased and adult emergence declined significantly with increase in concentration. Higher concentrations of β-caryophyllene caused pupal and adult deformities. A negative impact of β-caryophyllene was also seen on the nutritional physiology of S. litura . Parameters such as relative growth rate, relative consumption rate, efficiency of conversion of ingested food, efficiency of conversion of digested food and approximate digestibility showed a significant reduction in a dose dependent manner. DNA damage assessed using comet assay revealed significant genotoxic effects at LC30 and LC50 concentrations. There was an increase in tail length, percent tail DNA, tail moment and olive tail moment. Phenol oxidase activity was suppressed at LC50 concentration with respect to control. Total hemocyte count also declined significantly at LC30 and LC50 concentrations as compared to control. β-caryophyllene induced genotoxic and cytotoxic damage affecting the growth and survival of S. litura larvae. Our findings suggest that β-caryophyllene has the potential to be used for the management of insect pests. Graphical abstract: Image 1 Highlights: β-caryophyllene exerted negative impact on growth and development of Spodoptera litura. Nutritional physiology of S. litura was also adversely affected. Comet assay revealed significant DNA damage. Total Hemocyte Count (THC) also declined significantly at LC30 and LC50 concentrations. Phenol oxidase activity was also suppressed compared to control.